Gender Responsive Police Services for Women and Girls Subject to Violence Due to Pandemic Covid-19 - Resdiana Resdiana; Artanti Artanti (Cakrawala Repositori IMWI, 2023)
This study aims to examine how responsive the Police are in the Women and Children Protection Unit (PPA) during the Covid-19 pandemic. The domino effect of the Covid-19 pandemic has implications for all sectors of people's lives. It does not only have an impact on the health aspect, but also the economic and social aspects of the community. This condition can cause new problems in the family, including violence. The increase in cases of violence against children and women, both verbal and nonverbal, according to Kandedes (2020), is one of the increases arising from the impact of economic and psychological aspects that increase along with the family's economic conditions. In addition, the decline in the purchasing power of the community, both in villages and in cities (Tristanto, 2020), can guarantee psychological conditions in the family, so that it can trigger pressure and cause excessive production in husbands and wives, and make children as an outlet (Hutabarat, et al. al, 2020). Based on data from the Online Information System for the Protection of Women and Children (SIMFONI PPA) it was noted that cases of violence against children in Indonesia during the period January 1 to September 23, 2020 reached 5,697 cases with 6,315 victims (Ikhsan. 2020). This figure increases when compared to data from the Indonesian Child Protection Commission in 2019 of 4,369 cases and in 2018 of 4,885 cases of child violence (Fakhri, 2020). The researcher uses an approach method, by reviewing various data and sources of journals, to obtain answers on how the PPA Police Unit provides services to cases of violence against women and children during the pandemic (2020 to 2021). The effectiveness of gender responsive services at the PPA Polri Unit by cooperating with various other relevant stakeholders, as well as motivation theory. What is expected by the researcher is the level of community satisfaction and the gender responsive service strategy of the PPA Polri Unit for women and children subject to violence. There is still a community towards handling criminal acts of violence against women and children.